Prediction of a positive circumferential resection margin at surgery following neoadjuvant chemotherapy for adenocarcinoma of the oesophagus. Issue 6 (22nd August 2019) - Knight, W R C; Yip, C; Wulaningsih, W; Jacques, A; Griffin, N; Zylstra, J; Van Hemelrijck, M; Maisey, N; Gaya, A; Baker, C R; Kelly, M; Gossage, J A; et al.
Abstract: Background: A positive circumferential resection margin (CRM) has been associated with higher rates of locoregional recurrence and worse survival in oesophageal cancer. The aim of this study was to establish if clinicopathological and radiological variables might predict CRM positivity in patients who received neoadjuvant chemotherapy before surgery for oesophageal adenocarcinoma. Methods: Multivariable analysis of clinicopathological and CT imaging characteristics considered potentially predictive of CRM was performed at initial staging and following neoadjuvant chemotherapy. Prediction models were constructed. The area under the curve (AUC) with 95% confidence intervals (c.i.) from 1000 bootstrapping was assessed. Results: A total of 223 patients were included in the study. Poor differentiation (odds ratio (OR) 2·84, 95 per cent c.i. 1·39 to 6·01) and advanced clinical tumour status (T3–4) (OR 2·93, 1·03 to 9·48) were independently associated with an increased CRM risk at diagnosis. CT-assessed lack of response (stable or progressive disease) following chemotherapy independently corresponded with an increased risk of CRM positivity (OR 3·38, 1·43 to 8·50). Additional CT evidence of local invasion and higher CT tumour volume (14 cm 3 ) improved the performance of a prediction model, including all the above parameters, with an AUC (c-index) of 0·76 (0·67 to 0·83). Variables associated with significantly higher rates of locoregional recurrence were pN status ( P  = 0·020), lymphovascular invasion ( P  = 0·007) and poor response to chemotherapy (Mandard score 4–5) ( P  = 0·006). CRM positivity was associated with a higher locoregional recurrence rate, but this was not statistically significant ( P  = 0·092). Conclusion: The presence of advanced cT status, poor tumour differentiation, and CT-assessed lack of response to chemotherapy, higher tumour volume and local invasion can be used to identify patients at risk of a positive CRM following neoadjuvant chemotherapy. Graphical Abstract: A positive circumferential resection margin (CRM) has been shown to be an adverse prognostic indicator after oesophagectomy for adenocarcinoma. Clinical tumour status, tumour volume, poor differentiation, lack of response following chemotherapy and radiological assessment of invasion can be used to predict CRM positivity in oesophageal adenocarcinoma. CRM assessment is still important